Insurance Coverage and Use of Hormones Among Transgender Respondents to a National Survey - Stroumsa, Daphna (Ann Fam Med, 2020)
PURPOSE: We undertook a study to assess the associations between barriers to insurance coverage for gender-affirming hormones (either lack of insurance or claim denial) and patterns of hormone use among transgender adults. METHODS: We used data from the US Transgender Survey, a large national sample of 27,715 transgender adults, collected from August to September 2015. We calculated weighted proportions and performed multivariate logistic regression analyses. RESULTS: Of 12,037 transgender adults using hormones, 992 (9.17%) were using nonprescription hormones. Among insured respondents, 2,528 (20.81%) reported that their claims were denied. Use of nonprescription hormones was more common among respondents who were uninsured (odds ratio = 2.64; 95% CI, 1.88-3.71; P <.001) or whose claims were denied (odds ratio = 2.53; 95% CI, 1.61-3.97; P <.001). Uninsured respondents were also less likely to be using hormones (odds ratio = 0.37; 95% CI, 0.24-0.56; P <.001). CONCLUSIONS: Lack of insurance coverage for gender-affirming hormones is associated with lower overall odds of hormone use and higher odds of use of nonprescription hormones; such barriers may thus be linked to unmonitored and unsafe medication use, and increase the risks for adverse health outcomes. Ensuring access to hormones can decrease the economic burden transgender people face, and is an important part of harm-reduction strategies.